2020
DOI: 10.1101/2020.04.11.021915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of short-chain fatty acids in the gut-brain axis in schizophrenia: contribution to immune activation and pathophysiology in humans and mice

Abstract: Objective: Gut microbiota dysbiosis and aberrant gut-brain functional modules including short-chain fatty acid (SCFA) production and long-lasting immune activation (IA) are presented in schizophrenia. Given the key roles of gut microbiota and SCFA in shaping immunity, we propose that dysbiosis-induced SCFA upregulation could contribute to IA and behavioral symptoms in schizophrenia. Design: Gut microbiota, SCFA, and IA biomarkers were compared between schizophrenic patients and healthy controls. The roles of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…These results suggested that the accumulation of propanoic acid may mediate the effects of PCCB knockdown, and partially explain how propionic acidemia could lead to neuropathological symptoms. These results also suggested the potential effects of short-chain fatty acids on SCZ risk, since short-chain fatty acids including propanoic acid, acetic acid, and butyric acid were found to be upregulated in serum of SCZ patients 44 .…”
Section: Discussionmentioning
confidence: 66%
“…These results suggested that the accumulation of propanoic acid may mediate the effects of PCCB knockdown, and partially explain how propionic acidemia could lead to neuropathological symptoms. These results also suggested the potential effects of short-chain fatty acids on SCZ risk, since short-chain fatty acids including propanoic acid, acetic acid, and butyric acid were found to be upregulated in serum of SCZ patients 44 .…”
Section: Discussionmentioning
confidence: 66%
“…72 Zhu et al quantified acetate, propionate, and butyrate in the feces of 78 patients and 80 controls who were selected randomly from the discovery set, and found that all three types of SCFAs in the feces of patients increased. 73 In addition, there was a significant correlation between SCFAs in the feces of patients and serum SCFAs.…”
Section: Role Of Intestinal Microbiota and Circadian Rhythms In Psychiatric Disordersmentioning
confidence: 95%